Medicines, state and markets : co-construction of state and pharmaceutical industry in South Africa - (:unkn) unknown (My University, 2019)
Access to medicines has been at the core of an extensive literature. They usually highlight the collision betweenhigh-cost patented medicines promoted by industry and their increasing pressure on health spending.The timeline of access to antiretroviral treatments in South Africa since the beginning of the XXIth century castsa light on the struggles between industrial models based on private property and the rise of a multi-level coalitionwhich promotes the right to health. These struggles are epitomized by medias during the “Pretoria trial” in 2000.This case betrays the thorny encounter between two international bundles of rights without giving any clue on theconcrete construction of universal medicines coverage policy in South Africa.This thesis broadens the issue of medicines regulation by overcoming the contradictions between market and publichealth. It shows that government and industry keep strong contacts which have a deep impact on the three pillarsof the medicines sector: health systems, industrial capacities and innovation.Medicines policies emanate from these historical fundamental interdependences which are at the basis of statebuilding. The shift of governmental priorities towards public health does not entail the ostracism of pharmaceuticalindustry but the total reshaping of relations between public authorities and industry. What is at scope in this thesisare the links between the configuration of medicines policies and the mutation of pharmaceutical industrial models.
Keywords: African Research